2015
DOI: 10.5539/ijef.v7n9p244
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Disclosure Practices in Kuwait

Abstract: The purpose of this research is set out to examine the firm social responsibility disclosure practices in Kuwait by analyzing 2012 annual reports of industrial and service firms listed on Kuwait Stock Exchange (KSE) to find out whether the level of social disclosure is influenced by firm-specific characteristics. The study showed that the majority of the firms somehow disclose social information and revealed that the level of firm social responsibility disclosure is influenced by firm size, profitability and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…Liquidity, public ownership, and firm age have no impact on CSR. This means that companies with high liquidity disclose less social responsibility reporting compared to companies with low liquidity, which are likely to publish more social responsibility information in their annual reports to satisfy the information requirements of their stakeholders (Ajmi et. al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Liquidity, public ownership, and firm age have no impact on CSR. This means that companies with high liquidity disclose less social responsibility reporting compared to companies with low liquidity, which are likely to publish more social responsibility information in their annual reports to satisfy the information requirements of their stakeholders (Ajmi et. al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To determine the level of social disclosure in Jordanian banks listed on ASE, a disclosure index was used. A pilot study was applied, by the researcher, on the discloser index containing a few of the firms 'annual reports (Al-Ajmi et al, 2015).…”
Section: Study Methodologymentioning
confidence: 99%
“…Saayday ( 2005) explored corporate social disclosure (CSD) practices in Kuwait as part of his three-country study (which also included Jordan and Bahrain) and found that legislation played a major role in explaining levels of disclosure. Al-Shammari (2008) and Al-Ajmi et al (2015) also focused on disclosure matters noting positive associations between levels of CSD and firm size.…”
Section: Kuwaitmentioning
confidence: 99%